The Impact of Decision Support Systems (DSS) on Employee Work Effectiveness: A Case Study of Telco 2 Segment 3 Operations at PT. Infomedia Nusantara - Fahlevi, Noval; Mahdiana, Deni (Jurnal Manajemen Bisnis, 2024)
This study examines the impact of decision support systems (DSS) on employee work effectiveness at PT Infomedia Nusantara. The study employs a quantitative causal design, with the research subjects being employees of PT Infomedia Nusantara in Operational Division Telco 2 Segment 3 and the research object being DSS and employee work effectiveness. The research population is all employees on Operational Division Telco 2 Segment 3, totaling 128 people. Data were collected through interviews, document recording, and questionnaires and then analyzed using simple regression analysis. The results of the study show that DSS has a significant influence on employee work effectiveness.